Quantitative MRI to Characterize the Nucleus Pulposus Morphological and Biomechanical Variation According to Sagittal Bending Load and Radial Fissure, an ex vivo Ovine Specimen Proof-of-Concept Study - Deneuville, Jean-Philippe; Yushchenko, Maksym; Vendeuvre, Tanguy; Germaneau, Arnaud; Billot, Maxime; Roulaud, Manuel; Sarracanie, Mathieu; Salameh, Najat; Rigoard, Philippe (Frontiers in Bioengineering and Biotechnology, 2021)
Background and context: Low back pain is a dramatic burden worldwide. Discography studies have shown that 39% of chronic low back pain patients suffer from discogenic pain due to a radial fissure of intervertebral disc. This can have major implications in clinical therapeutic choices. The use of discography is restricted because of its invasiveness and interest in it remains low as it represents a static condition of the disc morphology. Magnetic Resonance Imaging (MRI) appears to be less invasive but does not describe the biomechanical dynamic behavior of the fissure. Purpose: We aimed to seek a quantitative MRI protocol combined with ex vivo sagittal loading to analyze the morphological and biomechanical changes of the intervertebral disc structure and stress distribution. Study design: Proof of concept. Methods: We designed a proof-of-concept ovine study including 3 different 3.0 T-MRI sequences (T2-weighted, T1 and T2 mapping). We analyzed 3 different mechanical states (neutral, flexion and extension) on a fresh ovine spine specimen to characterize an intervertebral disc before and after puncturing the anterior part of the annulus fibrosus. We used a mark tracking method to calculate the bending angles and the axial displacements of the discal structures. In parallel, we created a finite element model to calculate the variation of the axial stress and the maximal intensity shear stress, extrapolated from our experimental boundary conditions. Results: Thanks to an original combination of specific nuclear relaxation time quantifications (T1, T2) of the discal tissue, we characterized the nucleus movement/deformation into the fissure according to the synchronous mechanical load. This revealed a link between disc abnormality and spine segment range of motion capability. Our finite element model highlighted significant variations within the stress distribution between intact and damaged disc. Conclusion: Quantitative MRI appears to provide a new opportunity to characterize intra-discal structural morphology, lesions and stress changes under the influence of mechanical load. This preliminary work could have substantial implications for non-invasive disc exploration and could help to validate novel therapies for disc treatment.